Desain Pembelajaran Berdasarkan Prinsip Pedagogi, Andragogi dan Heutagogi - Kurniati, Yeli; Yuliana, Arwis; Amra, Abhanda (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to examine instructional design based on the principles of pedagogy, andragogy and heutagogy within the context of Islamic education. The study employs a qualitative approach through a systematic literature review of relevant articles from reputable journals, academic books and conference proceedings. Data were analysed using thematic analysis to identify patterns related to learner autonomy, instructional control, and learning outcomes. The findings indicate that instructional design is a dynamic and integrative process that must be capable of adapting to the diversity of learners’ characteristics. Pedagogy, andragogy, and heutagogy are understood as a continuum of learning approaches reflecting a shift from teacher-centred learning towards self-directed and self-determined learning. In the context of Islamic education, these three approaches complement one another as they align with the integration of intellectual, spiritual, and moral aspects. This study highlights the fundamental differences between the three approaches in terms of the roles of learners and educators, learning orientation, and evaluation strategies; consequently, an integrated instructional design model is required to address the challenges of contemporary education